Arteriogenesis egy uj terapias intervencios strategia kronikus arteriabetegsegekben. Sejtes mechanizmus es kiserletes modellek. - Erdő Franciska; Buschmann IR (ORVOSI HETILAP, 2007)
The term arteriogenesis became clarified only some years ago. This endogenous process is a natural compensation mechanism against stenosis or arterial occlusion-induced tissue hypoperfusion via improvement of blood distribution in the pre-existent collateral arteries. The main chronic artery disorders like coronary heart disease, peripheral artery disease and cerebrovascular disease were extensively studied for angiogenesis and arteriogenesis during the last decade. The in vivo animal experiments and the ex vivo analysis of the cellular and molecular mechanisms behind collateral artery development revealed the crucial role of circulating monocytes, endothelial and smooth muscle cells in the remodelling of collateral blood vessels. The adaptive arteriogenesis in the heart, brain and periphery can be stimulated by different chemokines and growth factors. The therapeutic application of these substances resulted in promising data in pre-clinical animal models, i.e. improved collateral conductance, extended neo-vascularization in the collateral dependent tissue regions, decreased infarct area after hemodynamic stroke and better functional parameters in myocardial ischemia. The questions that have to be addressed during the design of human investigations are the optimal delivery approach, the appropriate dosage, timing and the durability of the follow up. The present review tries to give an overview about the main points of the mechanism and the most important experimental data concerning spontaneous and stimulated collateral artery growth, this new and promising therapeutic approach for chronic artery diseases.